Introduksi Teknik Seduh Kopi Serta Coffee Mixology Di Desa Donowarih, Kecamatan Karangploso, Kabupaten Malang Dalam Upaya Mendukung Pembangunan Ekonomi Kreatif - Sunarharum, Wenny Bekti (Journal of Innovation and Applied Technology, 2024)
Donowarih Village is a village located in Karangploso District, Malang Regency which produces local specialty coffee and is located on a strategic position. The aim of this program was to introduce coffee brewing techniques and coffee mixology to representatives of the Donowarih Village community, in order to support creative economic development. The methods involved preparation, training, Focus Group Discussion (FGD), as well as technology introduction and technical supervision. The technology introduced was manual brewing techniques and coffee mixology, the technique of blending and mixing ingredients. The training went smoothly, attended by 5 participants from Donowarih Village. The result showed an increase of participants' understanding on manual brewing techniques and coffee mixology in order to increase enjoyment, sensation, and consumer acceptance.